Coupling and decoupling of Au and As in pyrite from Carlin-type Au deposits, southwest China. (1st May 2023) - Lin, Shiru; Hu, Kai; Cao, Jian; Liu, Yin; Liu, Shengjun; Zhang, Bin
Graphical abstract: Highlights: Gold and As contents in pyrite from Carlin-type Au deposits may be coupled or decoupled. High As contents in pyrite favor Au incorporation, but are not solely responsible for Au enrichment. The variable evolution of ore-forming fluids in the Youjiang Basin led to the various relationships of Au and As in pyrite. Gold precipitation was controlled by the extrinsic fluid conditions and microscopic reactions at the fluid–mineral interface. Abstract: The low-temperature geochemistry of gold (Au) and arsenic (As) in pyrite from Carlin-type Au deposits is significant for understanding the enrichment mechanisms of Au in pyrite, but remains poorly understood due to the complex processes that lead to the precipitation of micron-scale pyrite grains. This paper concerns the geochemical behaviors of Au and As during the precipitation of pyrite from six Carlin-type Au deposits (the Nibao, Shuiyindong, Banqi, Jinya, Yata, and Zimudang deposits), southwest China. These deposits are located in different locations and ore-bearing horizons of the Youjiang Basin. Arsenian pyrite and/or arsenopyrite are the dominant Au-bearing minerals. Gold-bearing pyrite grains are typically zoned (core, intermediate, and rim), with multiple, oscillatory banded sub-zones. In situ analysis demonstrates that invisible Au exists mainly as cationic Au + in the growth zones of pyrite. Gold and As are positively correlated (i.e., coupled) in the Nibao and Shuiyindong deposits, negatively correlated in the Banqi, Jinya, and Yata deposits, and poorly correlated in the Zimudang deposit. Arsenic and S substitution in pyrite and the presence of a reduced fluid promoted the incorporation of Au, resulting in the coupling of Au and As. The Au precipitation was affected by changes in the physicochemical conditions of the hydrothermal systems, independent of the As concentration, resulting in decoupling of Au and As. As such, invisible Au precipitation is controlled by the extrinsic physicochemical conditions of the ore-forming fluids and microscopic reactions at the fluid–mineral interface, and also the episodic incursion of Au-rich hydrothermal fluids. High As contents in pyrite favor Au incorporation, but are not solely responsible for Au enrichment. Gold and As contents in pyrite in Carlin-type Au deposits may be coupled or decoupled.